THE STRUCTURE OF MANGROVE COMMUNITIES IN THE KUALA ALAM VILLAGE OF THE SELAT BENGKALIS RIAU PROVINCE - Rivilgo, Wawan; Tanjung, Afrizal; Ghalib, Musrifin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was conducted in April 2017, in the mangrove forest area in the waters of The District Bengkalis Riau Province. The aim ofthis researchis to analyze the structure of mangrove communities and to know the condition of the environmental parameters. The method used in is the transect plot line method. The data obtained were analyzed for density, relative density, relative frequency, dominance and important value index. The results showed that the community of mangrove forest in the village of Kuala Alam consists of Avicennia lanata, Bruguiera cylindrica, Bruguiera gymnorrhiza, Rhizopora apiculata and Nypa fructicans. Rhizopora apiculata dominate in station I, II and III. This marked the highest value at all levels. The index value of diversity (H ') ranged from 1.0979 - 1.6974, shows that in this study area the level of medium diversity and mangrove conditions of this area is still quite good. The value of the dominance index (C) ranges from 0.35088 - 0.55120, indicates no individual dominant.Keywords: Mangrove Structure, Kuala Alam.